The Effect of Company Characteristics on Earnings Management - Ni Nyoman Ayu Suryandari; AA. Putu Gede Bagus Arie Susandya; Desak Made Mya Yudia Sari (AIBPM Publisher, 2023)
Earnings management constitutes the strategic orchestration by a managerial entity in the presentation of financial statements, aimed at inflating or deflating reported profits. The objective of this study is to scrutinize the impact of specific financial factors, namely liquidity, profitability, firm size, leverage, and managerial ownership, on the dynamics of earnings management. The research encompasses a population of 194 manufacturing companies listed on the Indonesia Stock Exchange during the period spanning from 2018 to 2020. From this population, a sample comprising 43 companies was diligently selected, employing the purposive sampling methodology. Subsequently, the data analysis technique applied to the sample set is multiple linear regression analysis. The findings of this empirical investigation shed light on the intricate relationship between the aforementioned financial factors and earnings management. Specifically, it is determined that liquidity and firm size do not exert a statistically significant influence on earnings management practices. In contrast, profitability, leverage, and managerial ownership are identified as factors that positively contribute to earnings management activities within this specific industrial and temporal context.